Konsep Kalimat Sawa' dalam Hubungan Antaragama: Analisis Komparatif Pandangan Hamka dan Nurcholish Madjid - Harda Armayanto; Adib Fattah Suntoro (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2022)
This paper seeks to explain kalimat sawa' in interreligious relations from the perspectives of Hamka and Nurcholish Madjid. Kalimat sawa' is a concept derived from Surah Ali Imran: 64 of the Qur'an frequently employed in interreligious relations. However, scholarly opinions on this concept differ. Some based this concept on religious pluralism, and some rejected it because it confirms that Islam is the only religion that Allah has blessed. Two notable Indonesian intellectuals, namely Hamka and Nurcholish Madjid, are associated with these two distinct concepts. This concept warrants further investigation because it is anticipated to be one of the approaches in interreligious relations. This type of research is qualitative and based on both printed and digital library research. Using comparative analysis, the author describes the perspectives of the two figures to be analyzed and compared in order to reveal their distinct thought patterns. According to Hamka, kalimat sawa' referred to in the Qur'an is an invitation to the Ahli Kitab group to return to monotheism, thereby establishing Islam as the only true religion. In contrast, Nurcholish Madjid interpreted the kalimat sawa' as an effort to unite religions on common ground. This idea is related to the concept of al-Islam as an attitude of submission to God so that no single religion has a monopoly on truth claims. Despite their differences, the idea of kalimat sawa' is an appropriate approach to interreligious relations, which is a similarity between the two.